2022
DOI: 10.1371/journal.pone.0274404
|View full text |Cite
|
Sign up to set email alerts
|

Poa annua: An annual species?

Abstract: As the Latin name annua implies, the species Poa annua L. is thought to have an annual life cycle. Yet, there are many reports in literature of P. annua persisting as a perennial. Considering that P. annua senescence patterns do not align with other true annual species, we hypothesized that P. annua is similar to other perennial, C3 turfgrass species that are subject to a confluence of environmental factors that can cause mortality. Four experiments were conducted in Knoxville, TN with the objective of determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The extensive reliance on herbicides for annual bluegrass control has resulted in high levels of herbicide resistance in certain plant populations and the belief that effective chemical control measures no longer exist (Heap 2023). In addition, although the Latin name annua implies that the species is an annual, recent research supports the hypothesis that Poa annua (annual bluegrass) is of a perennial life cycle and can be influenced by environmental conditions (Carroll et al 2022). Consequently, annual bluegrass prevalence on US golf courses is not likely to change in the foreseeable future.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The extensive reliance on herbicides for annual bluegrass control has resulted in high levels of herbicide resistance in certain plant populations and the belief that effective chemical control measures no longer exist (Heap 2023). In addition, although the Latin name annua implies that the species is an annual, recent research supports the hypothesis that Poa annua (annual bluegrass) is of a perennial life cycle and can be influenced by environmental conditions (Carroll et al 2022). Consequently, annual bluegrass prevalence on US golf courses is not likely to change in the foreseeable future.…”
Section: Resultsmentioning
confidence: 77%
“…Brosnan et al (2022) reported that the distribution of warm-and cool-season turfgrass species on putting greens across the United States differed from historical maps of growing zones, and suggested that the shift could be associated with a changing climate. Brosnan et al (2022) found that nearly 87% of survey respondents indicated that winter protective covers were used to maintain bermudagrass putting greens, including 100% of respondents in the US Transition region states of Kentucky, North Carolina, Tennessee, and Virginia. These protective covers are typically used when low-temperature injury is expected (DeBoer et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Also, higher nitrogen application rates can increase annual bluegrass in turfgrass swards (Dest & Guillard, 1987; Skogley, 1975). Annual bluegrass encroachment is often positively affected by frequent irrigation (Cain et al., 2021) and frequent fungicide applications (Carroll et al., 2022). Additionally, annual bluegrass resumes active growth earlier in the spring than other desirable turf species, providing a competitive advantage (Vargas & Turgeon, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…P. annua can be found on all seven continents globally (Chwedorzewska, 2008) and is referred to by various common names, including: annual meadowgrass, annual bluegrass, wintergrass, junegrass, suffolkgrass, speargrass, and walkgrass (Gibeault, 1971). Morphological diversity among P. annua is wide-ranging and its characterization as an annual species has been questioned, given that it does not exhibit monocarpic senescence (Carroll et al, 2021a;Carroll et al, 2022).…”
Section: Introductionmentioning
confidence: 99%